Effect of Incorporation of Potato on the Quality of Restructured Spent Hen Meat Blocks - Gupta, Swati; Sharma, B.D.; Mendiratta, S.K.; Irshad, A. (Journal of Meat Science, 2015)
The aim of this study was to evaluate the effect of incorporation of potato (Solanum tuberosum) on the physico chemical and sensory quality of restructured spent hen meat blocks. Three levels of potato (boiled and mashed) viz. 8%, 12% and 16% were incorporated by replacing the lean meat in pre-standardized restructured spent hen meat blocks formulation. A significant increase (P<0.05) in the pH of restructured spent hen meat blocks with increase in the level of potato was observed. The protein, fat and ash percentage of restructured spent hen meat blocks declined significantly (P<0.05) with incorporation of potato as compared to control. Moisture to protein ratio of all three treatments were significantly higher (P<0.05) than control. Mean sensory scores of restructured spent hen meat blocks incorporated with different levels of potato for general appearance and texture were comparable to control. Potato incorporation at 12% level found to be optimum for preparation of restructured spent hen meat blocks.